Large shareholders and firm performance—An empirical examination of founding-family ownership - Andres, Christian (Journal of Corporate Finance, 2008)
Using panel data on 275 German exchange-listed companies I examine the relationship between founding-family ownership and firm performance. By separating the family effect from general blockholder effects, the paper shows that family firms are not only more profitable than widely-held firms but also outperform companies with other types of blockholders. However, the performance of family businesses is only better in firms in which the founding-family is still active either on the executive or the supervisory board. These findings suggest that family ownership is related to superior firm performance only under certain conditions. If families are just large shareholders without board representation, the performance of their companies is not distinguishable from other firms. In addition, the results indicate that other blockholders either affect firm performance adversely or have no detectable influence on performance measures.